Case report: Multi-site perfusion strategy for type A acute aortic dissection complicated with cerebral malperfusion - Besa, Santiago; Castelli, Fiorenza; Garrido-Olivares, Luis; González, Rodrigo; Marine, Leopoldo; Becker, Pedro (Frontiers in Cardiovascular Medicine, 2023)
Acute type A dissection presenting with cerebral malperfusion has high morbidity and mortality. Given the complexity of underlying vascular involvement, it is a challenging clinical scenario. Many of these patients are not deemed surgical candidates. If surgery is considered, it often requires complex aortic arch and neck vessel reconstruction. We present a 48-year-old male with an acute type A aortic dissection that presented with paraplegia and decreased level of consciousness. A Computed Tomography showed occlusion of both common carotid arteries. He was successfully treated with a multi-site perfusion strategy and a Hybrid Frozen Elephant Trunk graft to achieve fast restoration of the cerebral circulation and minimize brain ischemia and permanent neurological damage. From this case, we learn that aggressive arch and neck vessel reconstruction supported by multi-site perfusion could help improve mortality and neurological outcomes in selected patients.